Influence of parturition and puerperium in the leucogram of Saanen goats (Capra hircus), raised in the State of São Paulo - Brazil - Birgel Júnior, Eduardo Harry; Viana, Rinaldo Batista; Ayres, Maria Consuelo Caribé; Benesi, Fernando José; Gomes, Viviane; Birgel, Eduardo Harry (Brazilian Journal of Veterinary Research and Animal Science, 2005)
With the intention of evaluating the influence of parturition and puerperium on the leukogram of Saanen goats (Capra hircus) 360 blood samples were collected from 20 goats and allotted into 18 experimental groups as described: 32, 16, 8, 4, 3, 2, 1 e ½ days before parturition, immediately after parturition, ½, 1, 2, 3, 4, 8, 16, 32 e 64 days after parturition. The blood samples were collected with EDTA and submitted to the following tests: total leukocyte counts, at the modified Neubauer hemocytometer, using Thomas liquid as a dilute and differential leukocyte count, made up with blood smears stained with Rosenfeld method. The evaluation of the leukogram showed significant variation that could be attributed to parturition and the puerperium. The leucograma became mostly neutrophilic at the end of pregnancy and puerperium. On the last three days of pregnancy, a gradual raise on the number of leukocytes was observed due to same changes on the total number of neutrophils. At the moment of parturition the leukogram was characterized by a leukocytosis due to neutrhophilia and lymphopenia. On the first 24 hours after parturition, it was still possible to observe this leukocytosis due to neutrophilia that disappeared on the subsequent days making the leukogram look similar to taht obseved at the late pregnancy until the end of puerperium.